2018
DOI: 10.1080/21642850.2018.1428103
|View full text |Cite
|
Sign up to set email alerts
|

Office workers’ beliefs about reducing sitting time at work: a belief elicitation study

Abstract: Objectives: Prolonged sitting has adverse health consequences, yet office workers can spend over 10 hours sitting each day. The Theory of Planned Behaviour may offer a useful perspective for understanding and enhancing psychological determinants of sitting at work. The aim of this belief elicitation study was to identify office workers' most salient beliefs relating to achieving the recently published Public Health England recommendation of accumulating at least two hours per day of standing and light activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…In other words, after the educational intervention, office employers were able to obtain necessary knowledge about perceived barriers to action and how to prevent it in order to perform a SE behavior. This finding of the present study was also consistent with the results of other studies 28,30,31. Barriers usually prevent the performance of SE behavior.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In other words, after the educational intervention, office employers were able to obtain necessary knowledge about perceived barriers to action and how to prevent it in order to perform a SE behavior. This finding of the present study was also consistent with the results of other studies 28,30,31. Barriers usually prevent the performance of SE behavior.…”
Section: Discussionsupporting
confidence: 94%
“…In Gill’s study, commitment to carry out a specific action at a given time and place has been verified as the most important structure for behavior change 25. Some similar studies of other models, for instance Stenberg et al26 and Roebuck et al,27 showed that commitment to a plan of action and the intention to carry out a particular health behavior were the most important factors for health behavior 28…”
Section: Discussionmentioning
confidence: 84%
“…Fourth, the affective rumination factor of leisure rumination was found to have a positive effect on the attitude and behavioral control factors of the modified theory of planned behavior. Affective rumination refers to employees experiencing a positive emotional state and mental recovery during work or in daily life through thoughts of leisure activity [ 17 , 21 , 87 , 88 ]. Moreover, this study identified that affective rumination may reduce negative emotional experiences by enabling employees to resolve work stress more actively through the pleasant recollection of leisure activities [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the aforementioned options are not accessible for many, are not environmentally sustainable, and are not practical and/or appealing enough for several people ( 62 , 159 , 160 ). This situation requires alternative approaches, such as for example, walking meetings, which has been reported to also lead to social benefits ( 161 ), as well as some recently proposed solutions with promising results, including intermittent upper body ergometry, an attractive option for those who prefer to remain in the seated position ( 162 ), and low-cost standing desks, which are made out of cardboard, are suitable for use in different locations such as at home, and can have an inexpensive and environment-friendly recycling process ( 163 , 164 ). Despite the challenges involved in implementing public policies that contemplate widespread access to PA promotion and sedentary behavior reduction initiatives, especially in low-income settings, localized comprehensive interventions have been recently implemented in many countries, including Canada and Brazil, and must be scaled up ( 60 , 101 , 146 , 165 ).…”
Section: Discussionmentioning
confidence: 99%